Hydrogen Bonding Interaction and Structural Change in Some Aliphatic Alcohol-Water Complexes: A Quantum Mechanical MP4 Study - Bezbaruah, Mrinal J.; Ahmed, Benzir; Ali, Ibrahim; Upadhyaya, Madhab; Bezbaruah, Bipul (Asian Journal of Chemistry, 2020)
Hydrogen bonding interaction in low molecular weight alcohols or lower alcohol (viz. methanol and ethanol) with water molecule is quite common. But, due to the presence of bulky groups in higher alcohols (viz. propanol, butanol and pentanol and their isomers) the hydrogen bonding interaction between alcohol and water molecule is significantly different. In alcohol-water heterodimer complexes, water plays an important role in the stability of such system, alcohol will be interacting with water molecule either as proton donor or proton acceptor mode. Quantum mechanical method, fourth degree Møller-Plesset (MP4) perturbation theory is an important tool for computing the interaction energy between the alcohol-water complexes. The interaction energy (IE) and natural bond orbital (NBO) calculations for some common aliphatic alcohol-water complexes (e.g. methanol, ethanol, propanol, butanol and pentanol) and their isomers were computed by using MP4 method.